A multicenter study of patients with multisystem Langerhans cell histiocytosis who develop secondary hemophagocytic lymphohistiocytosis. Issue 6 (6th December 2018) - Chellapandian, Deepak; Hines, Melissa R.; Zhang, Rui; Jeng, Michael; van den Bos, Cor; Santa‐María López, Vicente; Lehmberg, Kai; Sieni, Elena; Wang, Yini; Nakano, Taizo; Williams, James A.; Fustino, Nicholas J.; et al.
Abstract: Background: Langerhans cell histiocytosis (LCH) is a rare myeloid neoplasm characterized by the presence of abnormal CD1a‐positive (CD1a + )/CD207 + histiocytes. Hemophagocytic lymphohistiocytosis (HLH) represents a spectrum of hyperinflammatory syndromes typified by the dysregulated activation of the innate and adaptive immune systems. Patients with LCH, particularly those with multisystem (MS) involvement, can develop severe hyperinflammation mimicking that observed in HLH. Nevertheless, to the authors' knowledge, little is known regarding the prevalence, timing, risk factors for development, and outcomes of children and young adults who develop HLH within the context of MS‐LCH (hereafter referred to LCH‐associated HLH). Methods: To gain further insights, the authors conducted a retrospective, multicenter study and collected data regarding all patients diagnosed with MS‐LCH between 2000 and 2015. Results: Of 384 patients with MS‐LCH, 32 were reported by their primary providers to have met the diagnostic criteria for HLH, yielding an estimated 2‐year cumulative incidence of 9.3% ± 1.6%. The majority of patients developed HLH at or after the diagnosis of MS‐LCH, and nearly one‐third (31%) had evidence of an intercurrent infection. Patient age <2 years at the time of diagnosis of LCH; female sex; LCH involvement of the liver, spleen, and hematopoietic system; and a lack of bone involvement each were found to be independently associated with an increased risk of LCH‐associated HLH. Patients with MS‐LCH who met the criteria for HLH had significantly poorer 5‐year survival compared with patients with MS‐LCH who did not meet the criteria for HLH (69% vs 97%; P < .0001). Conclusions: Given its inferior prognosis, further efforts are warranted to enhance the recognition and optimize the treatment of patients with LCH‐associated HLH. Abstract : Langerhans cell histiocytosis (LCH)–associated hemophagocytic lymphohistiocytosis (HLH) is a rare hyperinflammatory phenotype of severe multisystem LCH that is associated with inferior survival. LCH‐associated HLH is most common in patients who are female; are aged <2 years at the time of diagnosis; and have LCH involvement of the liver, spleen, and/or hematopoietic system, and in 31% of cases, HLH develops in conjunction with an intercurrent infection.